Ferramenta de código aberto para simulação em acústica de salas na região de baixa frequência - Soares, Murilo Cardoso (2021)
In this work, a tool for low frequency room acoustics simulation is presented. It is written in Python and the Boundary Element Method is used. Practical aspects related to the characterization of sound sources and materials are discussed. With regard to the sound sources, they are initially considered as monopoles adjusted according to the frequency response of the source. The other possibility explored is the use of the spherical harmonics technique, which allows the characterization of its directionality. Concerning to material characterization, the Boundary Element Method requires surface impedance data, which are complex values. However, most of the data available to characterize the absorption of materials is in terms of real values of absorption coefficients. To deal with it, it is applied a method that allows to obtain complex valued surface impedances from real valued absorption coefficients. This method is based on solving an optimization problem. The simulation results are compared to measurements in a real room. These results highlight the need of a good characterization of the sound source and that the source directionality does not seem to have much impact on the results obtained for the frequency range analyzed. Furthermore, the consideration of complex-valued surface impedances seems to have a greater impact on the simulation results for rooms with higher absorption.